Dimalononitrile-containing probe based on aggregation-enhanced emission features for the multi-mode fluorescence detection of volatile amines. (28th November 2016) - Kong, Lingwei; Zhang, Yahui; Mao, Huiling; Pan, Xiaoling; Tian, Yong; Tian, Zhonglin; Zeng, Xiangkai; Shi, Jianbing; Tong, Bin; Dong, Yuping
Abstract : A novel multi-mode probe consisting of a hexaphenyl-1, 3-butadiene derivative, 2, 2′-((((1 Z, 3 Z )-1, 2, 3, 4-tetraphenylbuta-1, 3-diene-1, 4-diyl)bis(4, 1-phenylene))bis(methanylylidene))dimalononitrile (ZZ–HPB–CN), with typical aggregation-enhanced emission (AEE) features was easily prepared for the highly sensitive and rapid detection of amine vapors. The ZZ–HPB–CN sensor, which was prepared by simply depositing ZZ–HPB–CN on filter paper, could detect low concentration vapors of volatile amines using fluorescence, ultraviolet and naked-eye detection. The limit of detection of the sensor was as low as 1 ppb for the fluorescence detection. The color change of the sensor caused by 1–10 ppm amine vapors could be observed under UV light or with the naked eye. The high sensitivity, quick response and easy operation of the probe give it great potential for real-life applications.